Revolutionizing Oral Cancer Care: The Therapeutic Potential of Coenzyme Q10 and Balanced Trace Metals - Baloch, Saeeda Rind; Memon, Ayaz Ali; khan, Wasid Ullah; Sanjrani, Manzoor Ahmed; shah, Komal (Current Analytical Chemistry, 2025)
<span class=
Keywords: coenzyme Q10 (CoQ10) analysis